Effect of the degree of crosslinking on the interfacial layer structure of poly(vinyl chloride) dispersed with crosslinked poly(n-butyl methacrylate) particles. Issue 8 (13th October 2017) - Nakamura, Yoshinobu; Matsumoto, Takuya; Miyazaki, Ken-ichi; Noda, Masayo; Takakura, Kazuki; Tsutsumi, Ryota; Fujii, Syuji; Fujiwara, Kazuko; Hikasa, Shigeki; Sasaki, Mariko
Abstract: The interfacial layer structure of a model incompatible polymer blend system was analyzed using 1 H pulse nuclear magnetic resonance (pulse NMR) spectroscopy. Non-crosslinked and crosslinked poly( n -butyl methacrylate) particles with a mean size of ca. 0.9 μm were prepared by seeded emulsion polymerization, and the degree of crosslinking was varied. The particles were powdered using a freeze-dry method and dispersed in poly(vinyl chloride) by melt blending. Dynamic mechanical analysis indicated that the non-crosslinked particles were completely compatible. In contrast, mutual diffusion of the polymer chains in the crosslinked particles was restricted within the particle/matrix interfacial layer. As a result, an incompatible phase structure in which the crosslinked particles were dispersed in the continuous phase was formed. Pulse NMR analysis indicated that the interfacial layer thickness was in the range of 17–98 nm. The thickness decreased with an increase in the degree of crosslinking in the particles. The interfacial layer thickness in the particles was approximately 10 times larger than that for the incompatible polymer pair. Tensile test results indicated that the elongation at break was dependent on the thickness of the interfacial layer. The yield stress was developed for the particles with high hardness that was independent of the interfacial thickness.